Animasi 3D untuk Media Sosialisasi Kanker Serviks pada Kelurahan Pekojan - Safitri, Nurul; Eriya, Eriya (POLITEKNIK NEGERI JAKARTA, 2016)
Cervical cancer currently ranks second list of cancer in women. This is attributable to the lack of public knowledge about cervical cancer. From the results of questionnaires distributed to the member of PKK Pekojan known that over 50% of people do not understand about cervical cancer. To avoid the increasing number of people who contract cervical cancer it takes a socialization. The goal, to help provide information about cervical cancer to communities in Kelurahan Pekojan. There are many ways to create a media socialization, one of which is to create an animation. Animation created to act as the introductory material cervical cancer, which will be explained in the motion graphic. The animation was created consisting of animated characters and animation assets. Testing method used is the alpha and beta test. Alpha testing is done to test the level of similarity with the original character of the animated character. While in beta test and the quality test results to see the animation through questionnaires by respondents consisting of PKK members Pekojan village itself. From the second test showed that by adding an animated 3D video output socialization cervical cancer then presented becomes more attractive, because there is a storyline that can facilitate PKK Village Pekojan understand the information conveyed.